Parent-offspring competition and natal dispersal at several spatial scales in the great tit, Parus major (2004)
Models predict that condition-dependent dispersal can be promoted by variation in the intensity of kin competition. In particular, natal dispersal should be reduced as the parents' chances of survival decrease with age. The response to parental age should depend on the offspring's sex because of the asymmetry of competition between the sexes. We tested these predictions in the great tit population of Wytham Wood (Oxfordshire) where adult survival was shown to be age-dependent. Natal dispersal within the wood was dependent on the mother's age but not on the father's. Whereas young males were not affected by the mother's age, young females were found to disperse less when their mother was old. This indicates that mother-daughter competition can promote dispersal in the species. The same response was found whatever the spatial scale at which natal dispersal was examined